Case Study Of Rebates: Accounting And Taxation In Company A - Sianne Elliani Rudiatin; Harti Budi Yanti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This case study examines the accounting and tax treatment complexities of rebate schemes in Company A, revealing significant discrepancies between financial reporting and tax compliance. The research identifies three critical issues: (1) systematic under-accrual of rebate liabilities due to limited access to real-time sales data from retailers, resulting in revenue overstatement that contravenes PSAK 1's accrual principle and PSAK 72's variable consideration requirements; (2) problematic timing differences between accounting recognition and tax deductibility, creating potential tax risks; and (3) agency problems stemming from information asymmetry between the principal and distributors. The study contributes to institutional theory by analyzing rebate practices in Indonesia's unique regulatory environment, while practically recommending improved estimation methodologies and enhanced transparency to better align accounting and tax treatments. These findings offer novel insights into the challenges of implementing global accounting standards (IAS 37) in local contexts.